Longe da Água: o percurso traumático do herói contemporâneo - Machado, Luiza Casanova (2016)
The contemporary corpus of Brazilian Literature has been revealing good (and young) writers in the past few years, for example, the Porto-alegrense Michel Laub, author of Longe da Água (2004), among other narratives. His work reflects a sensibility in the way he grasps events apparently without a great dramaticity or consistency, but which will trigger dramatic or traumatic consequences. From a critical and specific observation of the compositional elements of his novel, this study will focus on the generating tension in the narrative language of Longe da Água. Therefore, in this research, this novel will be analyzed and interpreted according to the theoretical postulates on genre and on the nature of the fictional representation. With the purpose of achieving the objective of understanding the way tension works in relation to the individual trajectory, against the problematics of time and its course, this novel will be investigated through the critical view provided by Brazilian and Western contemporary literary production, that map out their main features and trends, specially those regarding the narrative. From this perspective, it will be possible to comprehend the manner the crisis between the self and time functions, transforming this relationship (subject-time) into a violent and traumatic relation.